Evaluation of Physical Properties of Soil Determinants Glucomannan Content of Porang Tuber (Amorphophallus muelleri) in Entisols of North Lombok - Febriana Sri Wahyuni; Sukartono Sukartono; Suwardji Suwardji (Jurnal Biologi Tropis, 2023)
Porang (Amorphophallus muelleri) is a tuber plant that contains the compound of glucomannan which has high economic value with a number of benefits, including as an industrial raw material. The glucomannan content of porang tubers has received special attention in research, including field research to determine soil properties that influence growth and content of gucomannan in porang tubers. A field survey has been carried out to determine the physical properties of soils that influence the glucomannan content of porang tubers grown in four clusters of agroforestry in the dry land of North Lombok, Eastern Indonesia. The results of the research showed that the physical properties of the soil that had a significant effect on the glucomannan content of porang tubers were soil bulk density (BD) with an R2 value of 53.15%, soil porosity with an R2 value of 60.23%, and silt particle fraction with an R2 value of 23. 47%. Thus, managing soil physical properties to facilitate the better quality of porang tubers is necessary.